Four-dimensional visualization of rising microbubbles - Jung, Ji Won (Nature Publishing Group, 2014)
Four-dimensional imaging, which indicates imaging in three spatial dimensions as a function of time, provides useful evidence to investigate the interactions of rising bubbles. However, this has been largely unexplored for microbubbles, mostly due to problems associated with strong light scattering and shallow depth of field in optical imaging. Here, tracking x-ray microtomography is used to visualize rising microbubbles in four dimensions. Bubbles are tracked by moving the cell to account for their rise velocity. The sizes, shapes, time-dependent positions, and velocities of individual rising microbubbles are clearly identified, despite substantial overlaps between bubbles in the field of view. Our tracking x-ray microtomography affords opportunities for understanding bubble-bubble (or particle) interactions at microscales – important in various fields such as microfluidics, biomechanics, and floatation.